Engaging South Asian Religions: Boundaries, Appropriations and Resistances, by Matthew Schmalz and Peter Gottschalk (eds.) - Zavos, John (Religions of South Asia, 2015)
Engaging South Asian Religions: Boundaries, Appropriations and Resistances, by Matthew Schmalz and Peter Gottschalk (eds.). Albany, NY: State University of New York Press, 2011. 253 pp. 75.00. ISBN 978-1-4384-3323-3 (hardback). 24.95. ISBN 978-1-4384-3324-0 (paperback).